(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Through the current study, through its sections, the researcher aims to show the impact of human resources management working in local restaurants, including the human resources working in foreign restaurants, and to study the comparison, similarities, and differences between them and what is the reason for the choice of the management of the reviewed restaurants between local and foreign human resources. The study began with a central problem represented by asking what the role played by the human resources that are the research subject and what the reason makes the foreign human resources targeted by the management of the researched restaurants. we dealt with the study from its applied aspect by selecting a group of restaurants in the holy city of Karbala that represents the research community, and the study was chosen from Restaurant management, or their owners (owners) are a sample for the research and in reality, and two main hypotheses for the research emerged. To answer the questions, achieve the study’s goal, and test the validity of the study’s ideas, the descriptive analytical approach was adopted as a fundamental approach to the research, and the questionnaire was used as an essential tool in all the data and information for the analysis. Several conclusions were reached through the study, the most prominent of which was (most human resources management in restaurants tend to employ individuals. Foreign workers are primarily employed for several reasons mentioned in the research)